Extraction of aluminum and iron from bauxite: A unique closed‐loop ore refining process utilizing oxalate chemistry. Issue 2 (9th October 2021) - Verma, Ankit; Corbin, David R.; Shiflett, Mark B.
Abstract: The Bayer process holds an exclusive status for alumina extraction, but a massive amount of caustic "red mud" waste is generated. In this work, three oxalate reagents: potassium hydrogen oxalate (KHC2 O4 ), potassium tetraoxalate (KHC2 O4 ·H2 C2 O4 ), and oxalic acid (H2 C2 O4 ) were investigated for the Al and Fe extraction process from NIST SRM 600 Australian‐Darling range bauxite ore. More than 90% of Al and Fe was extracted into the aqueous phase in less than 2 h with 0.50 M C 2 O 4 2 − for all three reagents. The Fe and Al can be selectively precipitated by hydrolyzing the aqueous phase. By acidifying the Al and Fe free filtrate, 80% of the C 2 O 4 2 − can be precipitated as KHC2 O4 ·H2 C2 O4 . Greater than 90% of the aqueous acid can also be recycled using a cation‐exchange resin. The proposed closed‐loop process is an energy‐efficient, cost‐effective, environmentally–friendly route for extracting Al and Fe from bauxite ore.